Chemical Preparation Routes and Lowering the Sintering Temperature of Ceramics - Philippe Colomban (Ceramics, 2020)
Chemically and thermally stable ceramics are required for many applications. Many characteristics (electrochemical stability, high thermomechanical properties, etc.) directly or indirectly imply the use of refractory materials. Many devices require the association of different materials with variable melting/decomposition temperatures, which requires their co-firing at a common temperature, far from being the most efficient for materials prepared by conventional routes (materials having the stability lowest temperature determines the maximal firing temperature). We review here the different strategies that can be implemented to lower the sintering temperature by means of chemical preparation routes of oxides, (oxy)carbides, and (oxy)nitrides: wet chemical and sol–gel process, metal-organic precursors, control of heterogeneity and composition, transient liquid phase at the grain boundaries, microwave sintering, etc. Examples are chosen from fibers and ceramic matrix composites (CMCs), (opto-)ferroelectric, electrolytes and electrode materials for energy storage and production devices (beta alumina, ferrites, zirconia, ceria, zirconates, phosphates, and Na superionic conductor (NASICON)) which have specific requirements due to multivalent composition and non-stoichiometry.